A New Psychovisual Threshold Technique in Image Processing Applications - Ernawan, Ferda (Faculty of Computer Systems & Software Engineering, Universiti Malaysia Pahang, 2016)
A psychovisual threshold is developed based on the psychoacoustic quite threshold. Psychovisual threshold is obtained from quantitative experiments by evaluating the just noticeable difference (JND) at various frequency orders. Psychovisual threshold is suitable to be implemented in image compression and image watermarking applications. In image compression, the experimental results produced largely free artifacts in the visual output image and better image quality at the higher compression rate than JPEG image compression. This technique is suitable to be used in image watermarking, the experimental results indicated that the proposed scheme can achieve high imperceptibility and robustness.